THE PROBLEMATIC ESSENCE OF THE EXPLANATION AND DEFINITION OF THE “TRUTH” - HAKOBYAN, GEVORG (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
All the spheres of scientific activity strive for the truth since the value of any scientific-philosophical statement depends on the trueness of the latter. So, here arises a proper question: is the essence of truth known by the scientificphilosophical community? If not, then how is it possible to assert that this or that mental structure is true? On the other hand, if it is known, it means that the essence of the truth can be defined or/and explained. Nevertheless, the analysis shows that any attempt to explain or define the essence of truth leads to a dead-end, i.e., it is simply impossible to define or explain the essence of the truth.